Różnice fluktuacji, dynamiki i dymorfizmu płciowego cech somatycznych, typu budowy i otłuszczenia dzieci i młodzieży w wieku od 4 do 18 lat - Mirosław Mrozkowiak; Paulina Jazdończyk (Kazimierz Wielki University, 2015)
Mrozkowiak Mirosław, Jazdończyk Paulina. Różnice fluktuacji, dynamiki i dymorfizmu płciowego cech somatycznych, typu budowy i otłuszczenia dzieci i młodzieży w wieku od 4 do 18 lat = Fluctuation, dynamics, sexual dimorphism, somatic features, body types and adiposity differences in children and adolescents at the ages from 4 to 18 from urban and rural areas. Journal of Education, Health and Sport. 2015;5(7):365-392. ISSN 2391-8306. DOI 10.5281/zenodo.20236 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A365-392 https://pbn.nauka.gov.pl/works/586309 http://dx.doi.org/10.5281/zenodo.20236 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 15.07.2015.   Różnice fluktuacji, dynamiki i dymorfizmu płciowego cech somatycznych, typu budowy i otłuszczenia dzieci i młodzieży w wieku od 4 do 18 lat   Fluctuation, dynamics, sexual dimorphism, somatic features, body types and adiposity differences in children and adolescents at the ages from 4 to 18 from urban and rural areas   Mirosław Mrozkowiak1, Paulina Jazdończyk2   1Bioergonsport, Nowa Biała magmar54@interia.pl strona: http://wadypostawy.republika.pl 2Gabinet Fizjoterapii Leszno Wlkp.   Słowa kluczowe: masa i wysokość ciała, typ budowy.   Streszczenie   Wstęp. Stan zdrowia badanej populacji, zgodnie z przyjętymi założeniami współczesnej ochrony zdrowia, znajduje także swoje odzwierciedlenie w poziomie oraz dynamice procesów wzrastania i dojrzewania. Jednym z istotnych czynników różnicujących osiągany poziom rozwoju fizycznego jest stopień zurbanizowania miejsca zamieszkania. Cel badań. Określenie istotności różnic między środowiskiem miejskim i wiejskim w przebiegu zmian wysokości i masy ciała, wskaźników BMI i IR w ramach każdej płci i kategorii wiekowej.  Materiał i metoda. Przeprowadzone badania w populacji 3806 dzieci i młodzieży w wieku od 4 do 18 lat, pozwoliły na zarejestrowanie 21895 obserwacji wysokości i masy ciała w poszczególnych kategoriach wiekowych, płci i środowisku, w tym 7199 dziewcząt ze środowiska miejskiego i 4484 ze środowiska wiejskiego, chłopców odpowiednio: 6426 i 3786. Określono typu budowy ciała według wskaźnika wagowo-wzrostowego Rohrera i otłuszczenia BMI. Pomiarów dokonano na wadze lekarskiej z dokładnością do0,5 cmi100 g.                 Wnioski. 1. Średnia wysokość i masa ciała badanych chłopców jest większa niż dziewcząt. Dynamika przyrostów w każdej z płci jest zbliżona, przy czym między13 a14 r.ż. występuje okresowy spadek tempa przyrostu obu cech. 2. Różnice w występowaniu typów budowy ciała osobników obu płci w środowisku miejskim i wiejskim zacierają się. W populacji żeńskiej są statystycznie nieistotne, natomiast w populacji mężczyzn istotne różnice występują w typie smukłym, gdzie odsetek występowania na wsi jest większy oraz w typie średnim, gdzie odsetek występowania w mieście jest większy. 3. Różnice w występowaniu typów otłuszczenia ciała osobników obu płci w środowisku miejskim i wiejskim zacierają się. W populacji żeńskiej są statystycznie istotne tylko w populacji posiadających nadwagę, częściej występują w środowisku miejskim. Natomiast w populacji mężczyzn istotne różnice występują w środowisku miejskim, osobników z nadwagą i niedowagą jest więcej.   Key words: body mass, body height, body type.   Summary   Introduction. Health condition of the studied population, according to the standards of contemporary health care, reflects itself in the level and dynamics of growth and maturation processes. One of the significant features differentiating the levels of physical development is the urbanization rate of one's place of residence.   Aims. The aim of the study is to determine the significance of differences in body mass and body height, as well as BMI and IR, between the individuals living in urban and rural environments, for both sexes and all age groups. Materials and methods. The study was conducted on 3806 children and adolescents at the ages from 4 to 18 and it enabled one to register 21895 body mass and body height observations in particular age groups, sexes and environments, including 7199 girls from urban areas and 4484 from rural areas, and 6426 boys from urban areas and 3786 from rural areas. Their body types were assessed according to Roher weight-height indicator, and their adiposity values according to BMI indicator; they were measured on a medical scale with accuracy to0.5 cmand100 g.  Conclusions. 1. Average body height and body mass of the studied male population is greater than of the female population; body mass and body height growth dynamics in both sexes are comparable, though at the ages from 13 to 14 one observes a decline in their increase pace. Differences in body types observed among the individuals of both sexes from urban and rural areas are gradually disappearing. In the female population they are statistically insignificant; in the male population, however, significant differences are observed in slim body type, whose percentage of occurrence is greater in rural areas, and in average body type, whose percentage of occurrence is greater in urban areas. 3. Adiposity differences between the individuals of both sexes living in urban and rural areas are gradually disappearing. In the female population they are statistically significant only among the overweight population which, in turn, is more numerous in cities. In the male population, however, significant differences are observed in urbanized areas among overweight and underweight individuals.